2020
DOI: 10.1097/inf.0000000000002848
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, Diagnostic Evaluation, Management, and Rates of Serious Bacterial Infection in Infants With Acute Dacryocystitis Presenting to the Emergency Department

Abstract: Background: Dacryocystitis is considered benign, yet infants represent a population at risk of complications. The presentation, management, and rates of serious bacterial infection in infants with dacryocystitis have not been described. Methods: We conducted a retrospective study of infants (12 months or younger) presenting to a single urban tertiary care pediatric emergency department between January 1995 and March 2014 with concern for dacryocystitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The lacrimal sac lies anterior to the orbital septum, which acts as a barrier to extension. Harris et al 12 found that 3/333 (1%) of infants (0-12 months) who presented to an emergency department with dacryocystitis had cellulitis, although it was not mentioned whether these were preseptal or orbital cellulitis. Prat et al 13 found similar rates (5/146, 3%) in pediatric patients with dacryocystitis in a tertiary hospital.…”
Section: Case Presentationmentioning
confidence: 99%
“…The lacrimal sac lies anterior to the orbital septum, which acts as a barrier to extension. Harris et al 12 found that 3/333 (1%) of infants (0-12 months) who presented to an emergency department with dacryocystitis had cellulitis, although it was not mentioned whether these were preseptal or orbital cellulitis. Prat et al 13 found similar rates (5/146, 3%) in pediatric patients with dacryocystitis in a tertiary hospital.…”
Section: Case Presentationmentioning
confidence: 99%